Pemodelan Segmentasi Sel Epitel Serviks Pada Citra Digital PAP SMEAR - Dedy Sofyan; Komariyuli Anwariyah (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
Cervical cancer is a disease that is very deadly. The level of this disease in Indonesia is very high, the rate of prevalence in 2013 of about 0.8% with an estimated 92 692 absolute throughout Indonesia. Early detection of cancer can be done with a Pap cytology examination. Slide readings performed by a specialist in anatomical pathology where normal conditions at least there should be 8000-12000 cells in good condition. This reading is not easy and has some constraints, it is necessary to melakkan designed system capable of automatically reading slide. System automation is expected to reduce errors due to manual readings. One of the stages in the building automation system is the segmentation of the cell to separate the cells from background objects. Separation is done by implementing the method of minima and maxima region, as well as the implementation of a subset of the region area. From this study, it was found that the model is implemented showed that the implementation of the model can be used to do the segmentation process either cell cytoplasm and nucleus.